Dampak Pertambangan Nikel di Pulau Kabaena terhadap Indeks Pembangunan Manusia (IPM) Bidang Pendidikan - Usman, Ashari; Suziman, Aris (Jurnal Kreatif Online, 2020)
Around 82.2 percent of land in Kabaena Island, Bombana Regency, Southeast Sulawesi is a nickel mining IUP area. To know whether the community becomes prosperous, the Human Development Index (HDI) is used to be the measurement, especially in the field of education. This study aimed to determine the HDI in the education sector which consists of two components, namely the average length of schooling (RLS) and the expected duration of schooling (HLS) in eight villages of mining area which are currently conducting exploitation. The results of this study indicated that the RLS of the mining area villages was 8.29 higher than the RLS in other areas of Bombana Regency around 7.54. Additionally, the average of HLS figure was 12.35, which was better than 11.81 of the Bombana Regency average. It shows that the presence of a mining company has affected the level of income and the welfare of thecommunity which has direct implications for the education sector. The company also provides CSR (Corporate Social Responsibility) funds with a value of hundreds of millions to billions of rupiah which are used by village governments and communities for infrastructure development, health and education development. In the field of education, the CSR funds are particularly used to provide allowances to teachers, teacher’s aide salary and scholarships to all students who are currently studying.